2012
DOI: 10.1039/c1cp22273b
|View full text |Cite
|
Sign up to set email alerts
|

A theoretical kinetic model of the temperature and pH dependent dimerization of orthosilicic acid in aqueous solution

Abstract: The first steps in a pH- and temperature-dependent theoretical kinetic model of silicate polymerization and dissolution are examined in this work with a combined ab initio and transition state theory based study of the dimerization of H(4)SiO(4). The role of solvation has been of primary concern in this work, and its influence on theoretical activation energies and pre-exponential factors has been thoroughly benchmarked. Relatively inexpensive MP2/6-31+G(d)//HF/6-31+G(d) calculations of octahydrate clusters, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
62
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(68 citation statements)
references
References 87 publications
6
62
0
Order By: Relevance
“…A widely-cited review 4 recommends multiplying the reactant symmetry numbers by a factor of two, referencing Pollak and Pechukas, though many studies involving identical reactants do not mention, and likely do not include, this factor of two. [5][6][7][8][9] Though a factor of two mistake can impact many phenomena, it causes huge errors in isotopic enrichment since the disputed factor of two is much larger than most non-hydrogen kinetic isotope effects. 10 This paper uses two methods to explain proper symmetry treatment in reaction kinetics.…”
Section: Introductionmentioning
confidence: 99%
“…A widely-cited review 4 recommends multiplying the reactant symmetry numbers by a factor of two, referencing Pollak and Pechukas, though many studies involving identical reactants do not mention, and likely do not include, this factor of two. [5][6][7][8][9] Though a factor of two mistake can impact many phenomena, it causes huge errors in isotopic enrichment since the disputed factor of two is much larger than most non-hydrogen kinetic isotope effects. 10 This paper uses two methods to explain proper symmetry treatment in reaction kinetics.…”
Section: Introductionmentioning
confidence: 99%
“…It has generally been reported that hydrolysis, condensation, and cyclization reactions are endothermic under different conditions [2,17,70,71,72,73], while solvation and hydrogen bonding are slightly exothermic [17]. The polymerization reaction of silanes obeys the Arrhenius equation (kh=AeEaRT), where k h is the rate constant, E a is the activation energy, R is the gas constant, and T is the absolute temperature.…”
Section: Hydrolysis and Early Stage Condensationmentioning
confidence: 99%
“…With the equilibrium Si isotope fractionation factors provided here, we could further explore the molecular-level clay mineral precipitation mechanisms by distinguishing the equilibrium isotope fractionations from the other processes. Previous theoretical works (He and Liu 2015;Rimstidt and Barnes 1980;McIntosh 2012;Nangia and Garrison 2008;Zhang and Liu 2014) all suggested that the polymerization of H 4 SiO 4 molecules needed to overcome a rather high activation energy barrier. Besides, the Si kinetic isotope fractionation of about -1.1 % determined by Geilert et al (2014) was identical to the Si equilibrium isotope fractionation between the monodentate 1 V[Fe 2 OSi(OH) 3 and the H 4 SiO 4 solution (He and Liu, 2015).…”
Section: Si Isotope Fractionation Between Clay and Solutionmentioning
confidence: 99%